2012
DOI: 10.1007/s00213-012-2866-y
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of alcohol hangover severity: development of the Alcohol Hangover Severity Scale (AHSS)

Abstract: The AHS, HSS, and AHSS all seem appropriate for application in hangover research. The use of a one-item hangover scale is not recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 18 publications
1
72
1
2
Order By: Relevance
“…The 23 items were derived from the Alcohol Hangover Severity Scale, the Hangover Symptoms Scale, and the Acute Hangover Scale 1214. The rationale for assessing individual hangover symptoms instead of using one of the three scales is the fact that they each list different hangover symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The 23 items were derived from the Alcohol Hangover Severity Scale, the Hangover Symptoms Scale, and the Acute Hangover Scale 1214. The rationale for assessing individual hangover symptoms instead of using one of the three scales is the fact that they each list different hangover symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…The amount of carbohydrates, proteins, fats, ethanol, methanol, propanol-1, butanol-2, isobutanol, butanol-1, 2-methyl-butanol-1 and 3-methyl-butanol-1 was determined. Hangover severity was assessed with the Alcohol Hangover Severity Scale, AHSS [34], and a 1-item hangover score. The analyses showed that hangover severity scores correlated significantly with the amount of carbohydrates, proteins, fats, ethanol, and congeners.…”
Section: Determinants Of Hangover Severitymentioning
confidence: 99%
“…For these 47 individual symptoms, the score reflected a single overall severity score for the hangover day. Using the symptoms present in the Alcohol Hangover Severity Scale (Penning et al., 2013), an overall hangover severity was computed.…”
Section: Methodsmentioning
confidence: 99%
“…Overall hangover severity is commonly assessed using 1 of 3 currently used scales (Penning et al., 2013; Rohsenow et al., 2007; Slutske et al., 2003). In all 3 scales, individual symptoms are scored with the sum or average representing the overall hangover severity score.…”
mentioning
confidence: 99%